Collective bargaining: building solidarity through the fight against inequalities and discrimination - Tailby, Stephanie; Moore, Sian (Cuadernos de Relaciones Laborales, 2014)
Equality bargaining in essence is turning the resource of collective bargaining to the objectives of equality and diversity in work and employment. This article traces the progress of equality bargaining, with a focus on the UK. It explores the decline of the coverage and scope of collective bargaining and increase in pay gaps on the vertical plane alongside extant social divisions and inequalities. It looks at legal solutions including statutory mechanisms to achieve collective bargaining and a National Minimum Wage. It notes that in the UK women are more likely to be covered by collective bargaining and despite a hostile economic climate, characterised by the fragmentation of bargaining through privatisation, that a union pay premium has survived and is larger for women. It discusses the limitations of both a National Minimum Wage and voluntary Living Wage for equality and concludes by supporting calls for the rebuilding of sectoral collective bargaining, but emphasises that this needs to be inclusive and expansive.